Decreasing Stigmatization: Reducing the Discrepancy Between “Us” and “Them”. An Intervention for Mental Health Care Professionals - Helmus, Kim; Schaars, Iris Kleine; Wierenga, Hansje; de Glint, Elise; van Os, Jim (Frontiers in Psychiatry, 2019)
Objective: Stigmatization has negative consequences for people with mental health disorder diagnosis. Studies indicate that professionals have stigmatizing attitudes and behaviour towards clients. Continuum beliefs are associated with less stigmatizing attitudes. The effect of a workshop to diminish stigmatizing attitudes and to enhance continuum beliefs is examined. Method: 202 mental health professionals from FACT teams were randomly assigned to a workshop or a waiting list control group. Stigmatizing attitudes and continuum beliefs were assessed in both conditions at baseline and follow-up. Results: Compared to baseline, the workshop group showed an increase on continuum beliefs. However, there was no effect of the intervention on stigmatizing attitudes. Contrary to the expectations, stigmatizing attitudes increased in the waiting list condition. Conclusion: Communicating the continuity aspect can be valuable in decreasing the ‘us and them’ discrepancy between professionals and people with mental disorders. Further research on continuum beliefs is needed.